Simulation of Tsunami Wave Spectra on Sri Lanka and Indonesia - Marghany , Maged; Hashim, Mazlan (Asian Association on Remote Sesning, 2006)
This work utilized the Quickbird satellite data to investigate the tsunami spectra run up along the coastal waters of Sri-Lanka and Indonesia. This work emphasized ocean wave propagation model provides with Delft software package to simulate the tsunami wave propagation in Malacca Straits. Edge detection algorithms of Soble and Canny used to determine coastal vegetation line changes due to the impact of tsunami event. The study obvious that the coastline of Indonesia exposed to high energy of tsunami wave compared Sri-Lanka coastline. The study shows too Canny algorithm has more precisely implementation in automatic detection of coastal vegetation line than Soble algorithm. It is interesting to predict next tsunami propagation in Malacca Straits. The forecasting model shows that tsunami wave will take 1 hour to reach Singapore coastal water within less than 4 m and takes 30 minutes to reach Penang Island within 15 m. It can be concluded that utilization different source of information and models can be used to draw good exploitation for tsunami mechanism impact and propagation.